Implementasi Batuk Efektif Untuk Meningkatkan Keefektifan Bersihan Jalan Nafas Pada Anak Dengan Bronkopneumonia Di Rumah Sakit Vita Insani Pematangsiantar - Fitriana Tasya; Eva Anita Yunia (LPPM Universitas Abdurrab, 2025)
Implementation Of Effective Cough To Increase The Effectiveness Of Airway Clearance In Children With Bronchopneumonia At Vita Insani Hospital in Pematangsiantar Implementasi Batuk Efektif Untuk Meningkatkan Keefektifan Bersihan Jalan Nafas Pada Anak Dengan Bronkopneumonia Di Rumah Sakit Vita Insani Pematangsiantar Fitriana Tasya*¹, Eva Anita Yunia² Students of the Kesdam I/BB Pematangsiantar Nursing Academy¹ Lecturer of the Kesdam I/BB Pematangsiantar Nursing Academy² ABSTRACT Background : Bronchopneumonia is an inflammation of the bronchi and alveolus of the lungs, which is the leading cause of infectious death in children under 5 years of age with 740,180 deaths in 2019 according to WHO. This disease is characterized by infiltrate patches due to bacterial, viral, or fungal infections with initial symptoms of upper respiratory tract infection, sudden high fever, restlessness, dispnu, rapid and shallow breathing and nasal lobes breathing, cough that is initially dry and then becomes productive. Effective coughing exercises are an intervention to train patients who do not have the ability to cough effectively to cleanse the larynx, trachea, and bronchioles of secretions or foreign bodies. Objectives : The purpose of this study was to give effective cough to increase the effectiveness of airway clearance in children with bronchopneumonia. Methods: This study uses a quantitative method with a descriptive research design of a case study approach with a total of 2 respondents in the Mahogany room at Vita Insani Hospital in Pematangsiantar. Datas had been taken on May 1, 2025 and June 3, 2025. Results: Evaluation results on An. V and An. A with an ineffective airway cleaning nursing problem indicates that the problem can be resolved. In clients 1 and 2 who initially had difficulty expelling sputum, after three days of effective coughing exercises, were able to increase effective coughing, decrease sputum production, and cope with breathing frequency well. Conclusion: The application of effective cough performed in bronchopneumonia patients is effective in improving airway effectiveness. This intervention can be used as a reference in nursing practice, especially in the treatment of bronchopneumonia patients. Keywords: effective cough, bronchopneumonia, clearness of airway, child ABSTRAK Latar Belakang : Bronkopneumonia adalah peradangan pada bronkus dan alveolus paru-paru, yang merupakan penyebab utama kematian menular pada anak dibawah 5 tahun dengan 740.180 kematian tahun 2019 menurut WHO. Penyakit ini ditandai oloh bercak infiltrat akibat infeksi bakteri, virus, atau jamur dengan gejala awal infeksi saluran nafas atas, demam tinggi mendadak, gelisah, dispnu, pernafasan cepat dan dangkal serta nafas cuping hidung, batuk yang awalnya kering kemudian menjadi produktif. Latihan batuk efektif merupakan suatu intervensi untuk melatih pasien yang tidak memilki kemampuan batuk secara efektif untuk membersihakan laring, trakea, dan bronkiolus dari sekret atau benda asing. Tujuan : Penelitian ini bertujuan untuk melakukan teknik batuk efektif dalam upaya meningkatkan keefektifan bersihan jalan nafas pada anak dengan bronkopneumonia. Metode: penelitian ini menggunakan metode kuantitatif dengan desain penelitian deskriptif pendekatan studi kasus dengan jumlah 2 responden diruang Mahoni di Rumah Sakit Vita Insani Pematangsiantar data diambil pada tanggal 1 Mei 2025 dan 3 Juni 2025. Hasil: Hasil evaluasi pada An. V dan An. A dengan masalah keperawatan bersihan jalan napas tidak efektif menunjukkan bahwa masalah tersebut dapat teratasi. Pada klien 1 dan 2 yang awalnya sulit mengeluarkan sputum, setelah tiga hari melakukan latihan batuk efektif, mampu meningkatkan batuk efektif, menurunkan produksi sputum, dan mengatasi frekuensi napas dengan baik. Kesimpulan: Penerapan batuk efektif yang dilakukan pada pasien bronkopneumonia efektif untuk meningkatkan keefektifan jalan nafas. Intervensi ini dapat dijadikan acuan dalam praktik keperawatan, khususnya dalam penanganan pasien bronkopneumonia. Kata Kunci: batuk efektif, pneumonia, bersihan jalan nafas, anak